2022
DOI: 10.33438/ijdshs.1093414
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of The Olympic Games and Doping Research

Abstract: Doping controls are carried out in all international mega sports organizations such as the Olympic Games to determine the use of doping. Prevention of doping use is carried out by the "Anti-doping Organization", WADA, which has an international participation structure. However, issues such as use of doping, doping agents, and using methods attract the attention of researchers. The research aims to analyze all scientific publications between 1980 and 2021 and to make a holistic analysis on doping using data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To this end, the publication years of the researches, reference change by years, authors, universities and the country publishing most have been identified to the profile, and the publications have been tried to be identified according to WOS (Web of Science) categorization. Bibliometric analyses enable the creation of the data that contribute the improvement of the interaction between countries and universities or supportive institutions by determining the researchers who publish most in the research field, academic journals and the most used keywords (Tabuk, 2022;Yıldız, et al, 2022). In addition, they also define important indicators such as especially author reference indices (h and q indices) in the creation of the performance data that reveal the productivity of countries, universities or authors (Merigó et al, 2020).…”
Section: Methods Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the publication years of the researches, reference change by years, authors, universities and the country publishing most have been identified to the profile, and the publications have been tried to be identified according to WOS (Web of Science) categorization. Bibliometric analyses enable the creation of the data that contribute the improvement of the interaction between countries and universities or supportive institutions by determining the researchers who publish most in the research field, academic journals and the most used keywords (Tabuk, 2022;Yıldız, et al, 2022). In addition, they also define important indicators such as especially author reference indices (h and q indices) in the creation of the performance data that reveal the productivity of countries, universities or authors (Merigó et al, 2020).…”
Section: Methods Bibliometric Analysismentioning
confidence: 99%
“…It also aims to contribute the determination of the topics missing in the literature, the key words used in researches, author interactions, focal point to be determined in further researches and etc. (Singh et al, 2023;Tabuk, 2022;Tabuk, 2023;Yerlı̇su-Pala & Köse, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analyse is an area of investigation which is based on stock-taking and through which the published books, magazines, articles and printouts of the cited texts are analysed by means of mathematical and statistical techniques (Al & Coştur, 2007;Meho, 2007;Pritchard, 1969;Yıldırım & Demir, 2019). Bibliometric analyses can be both in descriptive (determining the number of books and articles published in a certain year) and evaluative (evaluating the effects of an article via citing-analyses) forms (Kuruthan et al, 2017;Tabuk, 2022). These analyses make it possible to exhibit the general view of a certain discipline through the statistical investigations of topics, articles, cited writers and sources (Zarifmahmoudi et al, 2013).…”
Section: Methods Bibliometric Analysismentioning
confidence: 99%